Malignant Lymphoproliferative Disorders of the Oral and Maxillofacial Region: Report of Two Institutions - Flores-Hidalgo, Andres; Bankhead, Alec; Murrah, Valerie; Padilla, Ricardo (Frontiers in Oral Health, 2022)
Background: Report the incidence of malignant hematologic neoplasms in the oral cavity according to the experience of the two oral and maxillofacial pathology institutions in North Carolina, USA. Methods: A 15-year retrospective review was carried out in the records of patients at ECU SoDM and UNC Adams SoD. Age, sex, location of the lesion, clinical impression, initial diagnosis, and the immunohistochemical and molecular markers were recorded for each subject. All diagnoses were reviewed according to the 2016 revision of the WHO classification of lymphoid neoplasms. Results: A total of 318 records from both institutions were reviewed. 70 males and 68 females with an average age of 60.7 comprised the study population. The most common neoplasm encountered was plasma cell myeloma, followed by diffuse large B-cell lymphoma, B-lymphoblastic lymphoma, and follicular lymphoma. We encountered mostly intraosseous tumors, with the posterior mandible and posterior maxilla being the most common locations. Twelve cases were identified initially as a periapical radiolucency. Conclusion: Our findings are concurrent with the existing literature regarding epidemiologic data. However, the type and location of tumors encountered do not, as the most common lymphoma in the oral cavity is diffuse large B-cell lymphoma, which typically presents in soft tissue. To aid in diagnosis and treatment, collection of data should continue over time so that eventually a more specific diagnostic profile of NC residents with these neoplasms can be made.